A qualitative study of patient perspectives of diabetes and diabetic retinopathy services in Vanuatu. (4th April 2021) - 'Ofanoa, Malakai; Aitip, Basil; Ram, Komal; Dalmia, Prarthana; Pal, Moneeta; Nosa, Vili; Goodyear‐Smith, Felicity
Abstract: Issue addressed: Diabetes mellitus is an increasing global health problem, particularly in Vanuatu, where it poses a major health burden. There is paucity of information on how patients in Vanuatu perceive diabetes, diabetic retinopathy, access to services and management, health promotion and intervention services to alleviate the issues. This study aimed to explore the perceptions of diabetic patients in Vanuatu on these issues, to help inform the design of health promotion materials and community activities to empower people to self‐manage and shape diabetic services that are integrated and people‐centred. Methods: Qualitative Talanga and Kakala Pacific research methodologies were applied. Participants were diabetic patients from both urban locations and rural villages in Vanuatu. Data were collected from four (two male, two female) focus group interviews and thematically analysed. Results: There were 26 participants. System failures became apparent, including the inability of the health care services to meet the complex needs of patients with diabetes. The protective factors to reduce the risk and increasing incidence of diabetes and diabetic retinopathy included comprehensive village‐based health promotion and community development programmes at the primary prevention level. Conclusion: This study described patients' experiences of their diabetic care and identified key barriers and facilitators of service delivery pathways. So what?: Vanuatu needs to expand nationwide health promotion and education programmes on nutrition and exercise, food insecurity and access through trade agreements and provide well‐trained nursing and medical specialists for early diagnosis and adequate management of diabetes that all people can access and afford.